Pathological complete response in a patient with pleural mesothelioma treated with immunotherapy: a case report - Faccioli, Eleonora; Grosso, Federica; Dell’Amore, Andrea; Delfanti, Sara; Zambello, Giovanni; Cerbone, Luigi; Canu, Gianluca; De Angelis, Antonina; Sambataro, Viola; Pezzuto, Federica; Barbieri, Paola; Pasello, Giulia; et al. (Frontiers in Oncology, 2024)
The role of immunotherapy in the multimodal treatment for pleural mesothelioma (PM) is still under investigation, particularly in the preoperative setting. Pathological complete response (pCR) has been previously described after chemotherapy and immunotherapy; however, there is no prior experience reported with immunotherapy alone before surgery. We report the case of a 58-year-old male with biphasic PM treated with immunotherapy, resulting in a major clinical partial response. Following a multidisciplinary evaluation between thoracic surgeons, medical oncologists, pathologists, radiologists and radiation oncologists, the patient underwent surgery with radical intent through a right extended pleurectomy/decortication (eP/D). Histopathological examination of the specimen confirmed a pathological Complete Response (pCR). This case supports the feasibility and potential efficacy of combining preoperative immunotherapy with surgery in the management of advanced PM.